Determinants of Forensic Accounting Techniques’ Choice on Fraudulent Practices’ Investigation in Nigeria: Moderating Effects of Cashless Policy - Akinadewo, Israel Seriki; Akinadewo, Jeremiah O.; Asaolu, Taiwo O.; Odewole, Philips O.; Adebiyi, Ifeoluwa M. (Archives of Business Research, 2024)
The issue of economic and financial crimes among other fraudulent practices in the past decades in Nigeria, has been in the front burner of scholars in regard to the potency of forensic accounting to tackle this menace. The choice of the techniques adopted for investigation purposes is argued to determine the success or otherwise of this. Thus, this study examined the determinants of forensic accounting techniques’ choice of practitioners in addition to the influence of cashless policy as a moderating factor. Research survey design was adopted for data collection through structured questionnaire on practitioners. Purposive sampling technique was used to determine the population and the sample size, which were 110 respondents. Data were analysed with the aid of descriptive and inferential statistics. Logistic regression results showed that size of fraud, organizational policies, and legal factors, have a positive but statistically insignificant effect, while educational attributes, industry attributes, professional fees, type of fraud, criminal evidence availability, and audit quality, showed a negative and insignificant effect on the forensic accounting techniques choice for fraudulent practices investigation. The results also depicted that the moderating variable (cashless policy) demonstrated a negative and insignificant effect on the relationship of the main variable, but with mixed results with individual components. This study, therefore, recommends that forensic accountants require a more in-depth knowledge of the respective technique and the type of the fraudulent practices, for effective and efficient forensic accounting investigation assignments.